Respuesta :

Answer:

X=4

Step-by-step explanation:

28−(3x+4)=2(x+6)+x

28+−1(3x+4)=2(x+6)+x(Distribute the Negative Sign)

28+−1(3x)+(−1)(4)=2(x+6)+x

28+−3x+−4=2(x+6)+x

28+−3x+−4=(2)(x)+(2)(6)+x(Distribute)

28+−3x+−4=2x+12+x

(−3x)+(28+−4)=(2x+x)+(12)(Combine Like Terms)

−3x+24=3x+12

−3x+24=3x+12

Step 2: Subtract 3x from both sides.

−3x+24−3x=3x+12−3x

−6x+24=12

Step 3: Subtract 24 from both sides.

−6x+24−24=12−24

−6x=−12

Step 4: Divide both sides by -6.

−6x

−6

=

−12

−6

x=2

Answer:

x = 2

Step-by-step explanation:

28 - 3x + 4 = 2x + 12 + x

24 - 3x = 3x + 12

     + 3x   +3x

24 = 6x + 12

-12          -12

12 = 6x

x = 2

ACCESS MORE